DASHBOARD INVENTORI PT. PETRA SEJAHTERA ABADI - Diana Christian; Dedi Trisnawarman; Zyad Rusdi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2019)
The goal in making the Dashboard System Inventory PT. Petra Eternal Peace is to help cultivate the company's inventory data in the form of excel into the Dashboard. Methods of analysis and design using Prototype Requirements to find out the business activities and the needs of the user as manager in pt. Petra Eternal Peace. In making this Dashboard using several tools that are used like 2017 SQL server, SQL Server, Visual Studio Data Tools and Tableau 18.3. The result of the creation of this Inventory is a Dashboard helps managers in doing analysis and monitoring inventory more quickly and easily.